2020
DOI: 10.3390/medicines7040018
|View full text |Cite
|
Sign up to set email alerts
|

Methylxanthines Inhibit Primary Amine Oxidase and Monoamine Oxidase Activities of Human Adipose Tissue

Abstract: Background: Methylxanthines including caffeine and theobromine are widely consumed compounds and were recently shown to interact with bovine copper-containing amine oxidase. To the best of our knowledge, no direct demonstration of any interplay between these phytochemicals and human primary amine oxidase (PrAO) has been reported to date. We took advantage of the coexistence of PrAO and monoamine oxidase (MAO) activities in human subcutaneous adipose tissue (hScAT) to test the interaction between several methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…Benzylamine oxidation by human adipose tissue preparations is totally abolished by semicarbazide inhibition as already reported [37], therefore due solely to SSAO/PrAO, and was impaired in the pres-ence of caffeine (Figure 7). This was in agreement with previous observations of caffeine inhibition of human PrAO [27]. In the concentration range 0.1-2.5 mM, caffeine inhibited human PrAO with a broadly mixed pattern of inhibition.…”
Section: Inhibition By Caffeine Of Prao and Mao Activities In Human Adipose Tissuesupporting
confidence: 93%
See 4 more Smart Citations
“…Benzylamine oxidation by human adipose tissue preparations is totally abolished by semicarbazide inhibition as already reported [37], therefore due solely to SSAO/PrAO, and was impaired in the pres-ence of caffeine (Figure 7). This was in agreement with previous observations of caffeine inhibition of human PrAO [27]. In the concentration range 0.1-2.5 mM, caffeine inhibited human PrAO with a broadly mixed pattern of inhibition.…”
Section: Inhibition By Caffeine Of Prao and Mao Activities In Human Adipose Tissuesupporting
confidence: 93%
“…Human adipose tissue readily oxidized tyramine and benzylamine as recently reported [27]. The inhibition of human MAO by caffeine, already described for recombinant enzymes by Petzer et al [24], was confirmed in human adipose tissue preparations: Ki was 0.33 mM and Ki' was 1.8 mM (mixed inhibition; data not shown).…”
Section: Inhibition By Caffeine Of Prao and Mao Activities In Human Adipose Tissuesupporting
confidence: 76%
See 3 more Smart Citations